Ultrasound as potential inhibitor of salmon louse infestation—A small‐scale study. (31st May 2018) - Skjelvareid, Martin H; Breiland, Mette S W; Mortensen, Atle
Abstract: The effect of ultrasound exposure during controlled infection with salmon lice, Lepeophtheirus salmonis, has been studied. Salmon were placed in tanks with salmon lice copepodids for 1 hr, while simultaneously being exposed to sound frequencies of 9.3, 21 or 54 kHz. The sound transducers were operated at maximum power levels, and the 9.3 kHz transducer generated the highest sound level (220.6 dB). Only the group exposed to 9.3 kHz displayed a significant reduction in louse infestation. However, the observed effect of ultrasound was relatively small, and in a practical implementation in sea cages, the sound intensity will be lower than that used in the experiments. It is also possible that the observed reduction in infestation is due to ultrasonic cavitation effects, which are only present at a very short range from the ultrasound source. We therefore do not consider ultrasound a feasible method for preventing attachment of salmon lice copepodids on salmon in cage farms.